ANALISIS USABILITY PADA SISTEM INFORMASI E-TOURISM EKOWISATA HUTAN MANGROVE NGURAH RAI DENGAN METODE COGNITIVE WALKTHROUGH DAN SYSTEM USABILITY SCALE (SUS) - Kadek Adi Saputra; I Ketut Putu Suniantara; I Nyoman Dwi Arysna Mahendra; Ayu Chrisniyanti (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Currently, UPTD Tahura Ngurah Rai has information system called E-Tourism Ecotourism Ngurah Rai Information System (Ekomang) provided information about the Ngurah Rai Mangrove Forest Park. This application is used as a medium for introducing flora and fauna. However, usability testing has never been conducted on this application. Therefore, this research aims to conduct usability testing on the Ekomang system to ensure that application runs well and meets user needs. This research uses two methods such as the cognitive walkthrough and system usability scale (SUS). The evaluation of cognitive walkthrough is conducted by five UPTD Tahura employees and general public who have never used the Ekomang to identify problems and aspects such as learnability, effectiveness, and efficiency. In contrast, the system usability scale (SUS) is used to measure satisfaction aspects by collecting data from 20 users who have used the Ekomang. This usability on the Ngurah Rai Mangrove Forest Ecotourism system is expected to benefit UPTD Tahura Ngurah Rai in understanding the system’s efficiency and effectiveness levels as well as providing evaluation material for further developmentt